LIFTING THE VEIL OF THE GDPR TO DATA SUBJECTS - Laura-Cristiana SPATARU-NEGURA; Cornelia LAZAR (Challenges of the Knowledge Society)
Every natural person is entitled to personal data protection regardless of his or her nationality, residence, race, age, gender, language, religion, political and other affiliations, ethnicity, social background and status, wealth, birth, education, social position or any other personal characteristic. Europe’s clock is now ticking with regards to data protection: just in a few days, on 25 May 2018, a new EU data protection framework - the Regulation (EU) 2016/6791, will apply and will be directly applicable in all the Member States. This new General Data Protection Regulation governs the processing by an individual, a company or an organisation of personal data relating to individuals in the EU. Having in view the impact this regulation has for the entire world, we consider that it should be very well analysed. The aim of this study is to raise awareness and improve knowledge of data protection rules established by the GDPR. It is recommended for legal professionals and non-specialist legal professionals, and other persons working in the field of data protection. Additionally, this study intends to provide guidance to data subjects as for their rights under the GDPR and to give some relevant examples from our daily life in which data breaches happen